PENGARUH CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN PADA UMKM KERIPIK AYRA DI KOTA TEBING TINGGI - Andiny; Putri Nabila Ningsih Sitorus; Willy Cahyadi; Imelda Mardayanti (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the effect of content marketing (X1) and electronic word of mouth (E-WOM) (X2) on purchasing decisions (Y) at Ayra Chips UMKM in Tebing Tinggi City. The method used is quantitative by distributing questionnaires filled out by 96 respondents selected using accidental sampling techniques in the period December 2024 to January 2025. The results of the analysis show that both X variables have a positive and significant effect on Y variables, where content marketing and E-WOM are able to increase purchasing decisions at Ayra Chips. Validity and reliability tests state that the questionnaire instrument used has a good level of validity and reliability. The coefficient of determination test shows that both X variables are able to contribute 55.6% to the Y variable. The results of the study are consistent with the theory that states that content marketing (X1) and E-WOM (X2) are important factors that influence purchasing decisions (Y).